The role of nursing against psychological violence in women's lives (Research, Society and Development, 2024)
This study aims to analyze how nursing professionals can improve their practices to cope with psychological violence against women, exploring the scientific, social, and personal dimensions of this action. A systematic review was conducted to assess the magnitude of the association between types of intimate partner violence (IVP) and mental health outcomes and to shed light on the wide variation in prevalence rates of IVP in women. The study is a systematic review and meta-analysis. The following databases were searched for in this study: Cochrane, MEDLINE, EMBASE, PsycINFO, PubMed, and Allied Health Literature, as well as Applied Social Science Index and Abstracts. The inclusion criteria for this study are as follows: quantitative studies published from 2019 to 2024 on exposure to IPV in women over 16 years of age, using validated measures and the role of nursing in psychological victim care. Thus, it is concluded that nursing professionals can act as active voices in defending women's rights, contributing to structural changes and more protective legislation. In this way, nursing consolidates itself not only as a care profession but as an active force in the construction of a fairer, safer, and more welcoming society for women who suffer from psychological violence.